First-line treatment options in metastatic renal cell cancer - Kapoor, Anil (Canadian Urological Association Journal, 2016)
The introduction of targeted therapy a decade ago revolutionized the treatment of metastatic renal cell carcinoma (mRCC). The current standard of care focuses on the inhibition of angiogenesis through the targeting of the vascular endothelial growth factor receptor (VEGFR) and the mammalian target of rapamycin (mTOR). Currently recommended first-line treatments in Canada include sunitinib, pazopanib, and temsirolimus. With the heterogeneity of mRCC disease, the choice of treatment is driven largely by prognostic factors.